Capturing and using CO2 as feedstock with chemical looping and hydrothermal technologies. (27th November 2014) - Demirel, Yaşar; Matzen, Michael; Winters, Carina; Gao, Xin
Summary Chemical looping technology for capturing and hydrothermal processes for conversion of carbon are discussed with focused and critical assessments. The fluidized and stationary reactor systems using solid, including biomass, and gaseous fuels are considered in chemical looping combustion, gasification, and reforming processes. Sustainability is emphasized generally in energy technology and in two chemical looping simulation case studies using coal and natural gas. Conversion of captured carbon to formic acid, methanol, and other chemicals is also discussed in circulating and stationary reactors in hydrothermal processes. This review provides analyses of the major chemical looping technologies for CO2 capture and hydrothermal processes for carbon conversion so that the appropriate clean energy technology can be selected for a particular process. Combined chemical looping and hydrothermal processes may be feasible and sustainable in carbon capture and conversion and may lead to clean energy technologies using coal, natural gas, and biomass. Copyright © 2014 John Wiley & Sons, Ltd.